(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article describes the process of nursing work in pediatrics: the method of organizing and providing nursing care to a healthy and sick child, as well as information about the nurse’s relationship with the sick child and his parents.